Selecting lifestyle entrepreneurship recovery strategies: a response to the COVID-19 pandemic - Dias, Á.; Silva, R.; Patuleia, M.; Estêvão, J.; González-Rodríguez, M. R. (Tourism and Hospitality Research, 2021)
The devastating context of the Covid-19 pandemic has created a new reality in which tourism has practically come to a standstill, a situation that must be reversed. This study focuses on the revitalization of businesses run by lifestyle entrepreneurs, a very significant class, of pivotal importance in innovation in the tourism sector. Specifically, this study aims to identify the most relevant indicators to select the recovery strategies of these entrepreneurs. Using the Delphi method combined with the Q-sort technique, a ranking of the indicators was produced on the basis of input from a panel of 26 senior managers and academics. The top five indicators were: creativity and innovation, level of innovation, qualification, startups number, and turnover volume. Findings reveal that the priority is on innovation and the qualification of the entrepreneurs. Only afterward do the traditional indicators of competitiveness of tourist destinations emerge.